Global environmental effects versus galaxy interactions - Perez, Maria Josefa (2009)
We explore properties of close galaxy pairs and merging systems selected from the Sloan Digital Sky Survey Data Release 4 in different environments with the aim to assess the relative importance of the role of interactions over global environmental processes. For this purpose, we perform a comparative study of galaxies with and without close companions as a function of local density and host halo mass, carefully removing sources of possible biases. We find that at low- and high-local-density environments, colours and concentration indices of close galaxy pairs are very similar to those of isolated galaxies. At intermediate densities, we detect significant differences, indicating that close pairs could have experienced a more rapid transition on to the red sequence than isolated galaxies. The presence of a correlation between concentration index and colours indicates that the physical mechanism responsible for the colour transformation also operates in the transformation of the luminous matter distribution. At fixed local densities, we find a dependence of the red galaxy fraction on dark matter halo mass for galaxies with or without a close companion. This suggests the action of host halo mass related effects. Regardless of dark matter halo mass, we show that the percentage of red galaxies in close pairs and in the control sample are comparable at low- and high-local-density environments. However, at intermediate local densities, the gap in the red fraction between close pairs and the control galaxies increases from ∼10 per cent in low-mass haloes up to ∼50 per cent in the most massive ones. Interestingly, we also detect that 50 per cent of merging systems populate the intermediate local environments, with a large fraction of them being extremely red and bulge dominated. Our findings suggest that in intermediate-density environments galaxies are efficiently pre-processed by close encounters and mergers before entering higher local density regions.